To find the values of the translated function \( y = f(x + 5) \), we need to substitute \( x + 5 \) for \( x \) in the original function.
Given the original function values:
| \( x \) | \( y = f(x) \) | |---------|-----------------| | -2 | 5 | | -1 | 2 | | 0 | 1 | | 1 | 2 | | 2 | 5 |
To find \( y = f(x + 5) \), we need to determine the input \( x + 5 \) for each output \( y \).
To do this we can determine the required value of \( x \) for each \( y \):
-
For \( y = 5 \): Find \( x \) such that \( x + 5 = -2 \) or \( x + 5 = 2 \).
- If \( x + 5 = -2 \), then \( x = -2 - 5 = -7 \).
- If \( x + 5 = 2 \), then \( x = 2 - 5 = -3 \).
- Therefore, both \( -7 \) and \( -3 \) can produce \( y = 5 \).
-
For \( y = 2 \): Find \( x \) such that \( x + 5 = -1 \) or \( x + 5 = 1 \).
- If \( x + 5 = -1 \), then \( x = -1 - 5 = -6 \).
- If \( x + 5 = 1 \), then \( x = 1 - 5 = -4 \).
-
For \( y = 1 \): Find \( x \) such that \( x + 5 = 0 \).
- If \( x + 5 = 0 \), then \( x = 0 - 5 = -5 \).
-
For \( y = 2 \): Already calculated above.
-
For \( y = 5 \): Already calculated above.
Now we'll summarize these transformations into the table for the translated function \( y = f(x + 5) \).
Translated Function
| \( x \) | \( y = f(x + 5) \) | |---------|--------------------| | -7 | 5 | | -6 | 2 | | -5 | 1 | | -4 | 2 | | -3 | 5 |
Final Answer:
Original Function:
| \( x \) | \( y = f(x) \) | |---------|-----------------| | -2 | 5 | | -1 | 2 | | 0 | 1 | | 1 | 2 | | 2 | 5 |
Translated Function:
| \( x \) | \( y = f(x + 5) \) | |---------|--------------------| | -7 | 5 | | -6 | 2 | | -5 | 1 | | -4 | 2 | | -3 | 5 |